Natura comună a artelor [Articol] - Morari, Marina (USARB, 2013)
All the arts exist in an organic and complex unity. The fundamental principle of arts imposes a level of generalization on the inner order of the work. In our century, a new acceptance is given to the concept of the art unity by updating an old idea about the synthesis of arts in searching for certain solutions once unimaginable. The common nature of the arts can be discovered at the existential level by intuition and at the action level by the artistic experience. The receiver of the art work accumulates an experience, as a result of which a community of spirit and culture is formed, which evaluates historically, enlarging the "inner horizon”, of the art consumer. As the ego of the art work creator they unify the tendencies constituting the essence of its epoch, so the receiver synthesizes, from the multitude of communication experiences with different arts, a generalized vision about the world, life, arts.
Keywords: the unity of arts; the common platform for arts; the artistic experience